Nonlinear finite‐time control of hydroelectric systems via a novel sliding mode method. Issue 1 (16th November 2022) - Zhang, Runfan; Ren, Xinyi; Mahmud, Md. Apel; Li, Huanhuan
Abstract: A nonlinear finite‐time sliding mode control is proposed in this paper for the governing of complex hydroelectric systems with the finite/fixed setting time. The proposed control method is derived from the finite‐time stability and sliding mode control theories. The finite settling time is calculated and bounded, not depending on the initial conditions of the system. The solution trajectory of the controlled hydroelectric system can reach the sliding manifold in a fixed settling time, regardless of initial values. Based on the Lyapunov theory, the controlled hydroelectric system also converges to a reference state within the fixed settling time. A simulation of a high‐dimensional hydroelectric system verifies the feasibility of the proposed method. In addition, a comparison between the proposed method and the conventional PID method demonstrates the advantages of the proposed method in the shorter settling time and smaller overshoot. The proposed control method allows for the design of a flexible controller and provides an improvement in dynamic performance.